Numerical study of the active earth pressure distribution on cylindrical shafts using 2D finite difference code - Abdelmadjid Meftah; Naïma Benmebarek; Sadok Benmebarek (Journal of Applied Engineering Science and Technology, 2018)
The present paper examine the distribution of the active pressure on a circular shaftembedded in granular material subjected to radial displacement. The deformation problem wassolved under axisymmetric conditions using explicit finite difference code FLAC (Fast LagrangianAnalyses of Continua). Based on the numerical results, the distribution of the active pressure withincreasing excavation depth is non-linear for all interface angle of the shaft, for different diametersand height of the shaft also for the all friction angles of the soil. When friction angle of the soil thatare less than, or equal to 10° the active pressure is linear. These results are summarized andcompared against previously published theoretical solutions and experimental results.